Relationship Satisfaction On The Performance Of Employees Working In The Department Of Transmigration Of Manpower And Transmigration Province Maluku Administration Department Of Commerce - Kalsum Lussy (Politeknik Negeri Ambon, 2015)
The purpose of this study, to determine how the relationship satisfaction to employee performance field transmigration on manpower and transmigration Maluku, methods of data analysis used in this paper is a qualitative analysis that outlines the opinions of experts and study of theory about the relationship with employee performance. The results showed that the correlation or relationship of job satisfaction with employee performance Transmigration field is level was 0.518, which means that if the variable satisfaction (independent variables) to increase or decrease will affect the performance variables (variables affected). To improve the performance of employees, the satisfaction is an important factor to note, in order to produce kualutas good job.